Tinjauan Hukum Islam dan UU No. 1/1974 terhadap Larangan Perkawinan Semarga Adat Batak Desa Tapian Nauli Iii Sumatera Utara - Siti Aisyah; Siska Lis Sulistiani; Shindu Irwansyah (UNISBA Press, 2023)
Abstract. The prohibition on same-sex marriages in the Batak Customary Village of Tapian Nauli III is a ban on same-sex marriages that has existed since the time of our ancestors. If you continue to carry out same-sex marriages, unwanted things will arise, such as family disputes, and avoiding the risk of genetic disorders that may arise as a result of marriages within the same clan. The perpetrators of the same clan marriage must receive very heavy sanctions, because it has been determined by the adat party and community agreement. This study aims to find out the review of Islamic law and Law No.1/1974 regarding the prohibition of same-sex marriages. This study uses a normative juridical approach using library data and field data in the form of interviews with the people of Tapian Nauli III Village, North Sumatra. Primary data sources were obtained from interviews, while secondary data came from the Koran, hadith, Marriage Law, Criminal Code, KHI, and journals related to research issues. Data analysis used descriptive qualitative. The results of the study concluded that the prohibition on marriage is appropriate and does not conflict with Islamic law because customary law is non-binding and only applies to the indigenous Batak community. In addition, the prohibition on same-sex marriages is in accordance with Law No. 1/1974 concerning marriage. Because it is not included in the prohibition of marriage in the Law, but in this case, the Marriage Law adheres to the principle of family participation, in which the agreement of parents as guardians becomes the benchmark when their children want to marry in the same clan because it refers to the validity of marriage. Abstrak. Larangan Perkawinan semarga Adat Batak Desa Tapian Nauli III merupakan suatu larangan perkawinan semarga yang ada sejak zaman nenek moyang. Apabila tetap melaksanakan perkawinan semarga maka akan timbul hal yang tidak diinginkan seperti percekcokan dalam Keluarga, dan menghindari resiko kelainan genetik yang mungkin timbul akibat perkawinan dalam semarga. Pelaku perkawinan semarga tersebut harus mendapatkan sanksi yang sangat berat, karena sudah di tetapkan oleh pihak adat dan kesepakatan masyarakat. Penelitian ini bertujuan untuk mengetahui tinjauan Hukum Islam dan UU No.1/1974 mengenai larangan perkawinan semarga. Penelitian ini menggunakan pendekatan yuridis normatif dengan menggunakan data pustaka dan data lapangan berupa hasil wawancara dengan masyarakat Desa Tapian Nauli III Sumatera Utara. Sumber data primer diperoleh dari hasil wawancara, sedangkan data sekunder dari al-Qur’an, hadist, UU Perkawinan, KUHPdt, KHI, dan jurnal-jurnal yang berhubungan dengan masalah penelitian. Analisis data menggunakan deskriptif kualitatif. Hasil penelitian menyimpulkan bahwa larangan perkawinan ini, sesuai dan tidak bertentangan dengan hukum Islam karena hukum adat itu sifatnya tidak mengikat dan hanya berlaku untuk masyarakat adat Batak. Selain itu, larangan perkawinan semarga sesuai dengan UU No.1/1974 tentang perkawinan. Karena bukan termasuk larangan perkawinan dalam Undang-Undang tersebut akan tetapi dalam hal ini, Undang-Undang Perkawinan menganut asas partisipasi keluarga yang mana persetujuan orang tua sebagai wali yang menjadi patokan ketika anaknya hendak melangsungkan perkawinan semarga karna mengacu kepada keabsahan Perkawinan.